Can transport infrastructure change regions' economic fortunes? Some evidence from Europe and China. Issue 1 (2nd January 2017) - Chen, Chia-Lin; Vickerman, Roger
ABSTRACT: Can transport infrastructure change regions' economic fortunes? Some evidence from Europe and China. Regional Studies . Claims and counterclaims about the likely impact of new transport infrastructure on a region's economic performance have existed for centuries going back to the early days of canals and railways. High-speed rail (HSR) as a new type of infrastructure has just over 50 years of existence. The persistent debate is questioning the power of HSR in reducing economic disparities between cities and effecting economic transformation. The paper goes beyond macro-modelling, looking to more disaggregated approaches of the structural changes. Two regions, one in Europe and one in China, are compared to gain insights for future research and practice.